EVIDENCE BASED NURSING (EBN): BLADDER TRAINING IN URINE ELIMINATION DISORDERS PATIENTS IN LABUANG BAJI MAKASSAR HOSPITAL - Risnah, Risnah; Yustilawati, Eva; Sudarmi, Sudarmi; Rosmah, Rosmah (Homes Journal: Hospital Management Studies Journal, 2022)
Bladder Training is one of the applications of Evidence Based Nursing (EBN) to reduce urinary elimination disorders in Chronic Kidney Disease (CKD) patients with urinary catheters. Bladder training is bladder training that aims to develop muscle tone and bladder sphincter muscles for maximum purpose. The purpose of this EBN is to identify the effectiveness of Bladder Training (delay urination) in reducing urinary elimination disorders in Chronic Kidney Disease (CKD) patients . The results of this EBN application were found that at the time of administering bladder training,on the first day the patient has not felt the sensation of wanting to urinate and at the time of giving bladder training on the second day the client has felt the sensation of wanting to urinate. Bladder training (delay urination) can be recommended as a non-pharmacological therapy to reduce urinary elimination disorders, is easy to do, safe and technically practical to reduce elimination disorders in Chronic Kidney Disease (CKD) patients